IntelFlow: Towards adding Cyber Threat Intelligence to Software Defined Networks - Ancieta, Javier Richard Quinto; Rothenberg, Christian Esteve (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2015)
Security is a major concern in computer networking, which faces increasing threats as the commercial Internet and related economies continue to grow. Our work aims to explore advances in Cyber Threat Intelligence (CTI) in the context of Software Defined Networking (SDN). More specifically, we propose IntelFlow, an intelligence detection system for Software Defined Networking (SDN) that follows a proactive approach using OpenFlow to deploy countermeasures to the threats learned through a distributed intelligence plane. We show through a proof of concept implementation that the proposed system is capable of delivering a number of benefits in terms of effectiveness, altogether contributing to the security of modern computer network designs.